2013
DOI: 10.1177/0972150913477470
|View full text |Cite
|
Sign up to set email alerts
|

A Wave of Mergers and Acquisitions: Are Indian Banks Going Up a Blind Alley?

Abstract: Mergers and acquisitions are strategic decisions taken for maximization of a company's growth. But the point of the matter is, how far does the empirical evidence support this notion? An examination of the existing literature suggested no conclusive evidence about the impact of M&A on corporate performance. Therefore, this article investigates the mergers in the Indian Banking industry to find out whether Indian banks have achieved performance efficiency during the post-merger period namely in the areas of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…The second method that we employ to compute the expected return is the most widely used MM (Barai & Mohanty, 2014;Brown & Warner, 1985;Kalra, Gupta, & Bagga, 2013;Kiymaz & Baker, 2008;MacKinlay, 1997;Rani, Yadav, & Jain, 2015a;Wu, Yang, Yang, & Lei, 2016;Yilmaz & Tanyeri, 2016). MM relates the company return with the market return, and it is formulated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…The second method that we employ to compute the expected return is the most widely used MM (Barai & Mohanty, 2014;Brown & Warner, 1985;Kalra, Gupta, & Bagga, 2013;Kiymaz & Baker, 2008;MacKinlay, 1997;Rani, Yadav, & Jain, 2015a;Wu, Yang, Yang, & Lei, 2016;Yilmaz & Tanyeri, 2016). MM relates the company return with the market return, and it is formulated as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Mantravadi and Reddy (2008) investigated Indian acquiring firms and found that there are minor variations in terms of impact on operating performance following mergers, in different sectors of Indian industries. Kaur (2010) analysed 'why some firms acquire' and 'why some get acquired' with special reference only to the Drugs and Pharmaceutical Industry from 1993-1994to 2002-2003. Kalra et al (2013 examined the firm-specific factors impacting M&As for the Indian banking sector and found the absence of any significant impact of M&As on their financial performance.…”
Section: Overview Of Literaturementioning
confidence: 99%
“…The analysis is based on the event study which has been applied in different contexts by many researchers. The methodology has been applied to gauge, among others, the impact of mergers and acquisitions (Anand & Singh, 2008;Kalra, Gupta, & Bagga, 2013), share buyback announcements (Chatterjee & Mukherjee, 2015) and dividend announcements (Maitra & Dey, 2012). The methodology has been used to assess the impact of marketing-related decisions like celebrity endorsements (Jaikumar & Sahay, 2015;Liu & Brock, 2011) and brand extension announcements (Lane & Jacobson, 1995).…”
Section: Empirical Modelmentioning
confidence: 99%